Establishment of Microwave Drying Dynamic Model for Foshou Leaves Powder and Analysis of Quality Characteristics - Hui SUN; Bo ZHANG; Jianghong ZHOU; Zhenyi XU; Zhixing MAO; Yuxiang WANG; Jie PANG (Shipin gongye ke-ji)
To enhance the drying efficiency and quality of Foshou leaf powder, this investigation assessed the effects of intermittent drying modes, microwave power, and load amount on its drying attributes and sensory qualities, utilizing dry basis moisture content, rate of dehydration, and sensory evaluations as benchmarks. The objective was to identify the most favorable drying conditions while also compare the variances in microstructure, color, chlorophyll concentration, hygroscopicity, solubility, and tea polyphenol between Foshou leaf powders dried using hot air and microwave techniques. The findings demonstrated that the intermittent drying modes of 20 and 30 seconds yielded the highest quality Foshou leaf powder, establishing these conditions as optimal. Notably, microwave power and the quantity of material loaded were determinants of drying speed, with an increase in microwave power notably shortening the drying duration, especially during the constant-rate phase of drying. Conversely, the effect of the load amount on drying speed was less pronounced during the falling-rate phase. Optimal sensory quality, scoring 16.5, was observed at a microwave setting of 385 W with a 20 g load amount. Through the comparison of three mathematical models to simulate drying kinetics, a nonlinear relationship between the moisture ratio of Foshou leaves and the drying time was observed. The Page and Wang-Singh models were particularly effective, with the Wang-Singh model providing superior predictive accuracy. The most accurate fitting function determined was MR=(0.0011+0.0058X1+0.0037X2)t2−(0.086+0.1544X1+0.086X2)t+1. In comparison to hot air drying, the Foshou leaf powder produced under optimal microwave drying conditions showed a looser and finer particle structure, a vibrant green hue, and enhanced sensory properties (16.9), alongside improved wettability, solubility, and a higher preservation of tea polyphenols and chlorophyll. These insights offer valuable scientific direction for the advanced processing of Foshou leaves, highlighting the potential of microwave drying in augmenting the quality of leaf powders.